FRI0455 Renal Function in Anca-Associated Vasculitis is Associated with ENT Involvement. (10th June 2014) - Rahmattulla, C.; de Lind van Wijngaarden, R.A.; Berden, A.E.; Hauer, H.A.; Floßmann, O.; Jayne, D.R.; Gaskin, G.; Rasmussen, N.; Noël, L.-H.; Ferrario, F.; Waldherr, R.; Wolterbeek, R.; et al.
Abstract : Background: It has been suggested that ear, nose, and throat (ENT) involvement in ANCA-associated vasculitis (AAV) may carry the advantage of earlier recognition of the disease. Alternatively, differences in histological findings between patients with MPO-ANCA and PR3-ANCA might represent different routes in the pathogenesis of vasculitic disease in these subsets of patients. Objectives: This study investigates whether ENT involvement in AAV is associated with better renal function and histopathology than AAV without ENT involvement. Methods: Newly diagnosed AAV patients with renal involvement from three international, multicentre trials were included. Multivariable analysis correcting for age, ANCA-serotype, tubulitis, interstitial infiltrate, interstitial fibrosis and tubular atrophy (IFTA), and the histopathological class in the classification of ANCA-associated glomerulonephritis (AAGN) investigated an association between ENT involvement and estimated glomerular filtration rate (eGFR). To investigate whether our findings are specific to ENT involvement, we repeated the multivariable analysis with cutaneous involvement, lung involvement, and arthralgia/arthritis as possible eGFR determinants. Results: Of the 414 patients included in this study, 185 patients had ENT involvement. Patients with ENT involvement had a better eGFR compared to patients without ENT involvement. Mean (SD) presenting eGFR of patients with and without ENT involvement was 39.2 (33.1) and 23.9 (20.1) mL/min/1.73 m 2, respectively (p<0.001). Moreover, average eGFR increased by 6.7 (95% CI 1.7 – 11.6) mL/min/1.73 m 2 with each additional ENT symptom present (p<0.008). Patients with ENT involvement also had less interstitial fibrosis and tubular atrophy in their renal biopsy (p<0.001) and a prognostically more favourable class in the histopathological classification of AAGN (p=0.044). Multivariable linear regression analysis to investigate associations with eGFR showed that, in addition to ENT involvement (β=9.0, p=0.004), age (β=-0.5, p<0.001), tubulitis (β=-8.1, p=0.001), interstitial infiltrate (β=-8.1, p<0.001), IFTA (β=-7.9, p=0.002), and the histopathological classification of AAGN (β=-6.5, p<0.001) were each independently associated with eGFR. A pre-specified sensitivity analysis including only PR3-ANCA positive patients showed that also in this subgroup of patients ENT involvement is positively associated with better eGFR. No influence on eGFR was observed with cutaneous involvement, lung involvement, or arthralgia/arthritis, suggesting that our findings are specific to ENT involvement. Conclusions: ENT involvement in AAV patients with renal disease is associated with better renal function and a prognostically more favorable renal biopsy. These findings are indicative of different phenotypes of AAV defined by ENT involvement. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1745